2017
DOI: 10.1111/jscm.12142
|View full text |Cite
|
Sign up to set email alerts
|

A Supply Chain Perspective on Strategic Foothold Moves in Emerging Markets

Abstract: Emerging markets present intriguing growth opportunities, but they are often extremely risky for foreign entrants. Given this riskiness, companies entering emerging markets may establish strategic footholds—small positions that they can later choose to expand (referred to as an attack) or abandon (referred to as a withdrawal)—rather than making costly large‐scale entries. While scholars have begun to examine the competitive dynamics surrounding footholds, the influence of the supply chain has not been consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
(81 reference statements)
3
22
0
1
Order By: Relevance
“…Second, we shed light on how emerging market footholds accentuate performance by proposing that they facilitate the acquisition of strategically valuable market‐specific knowledge, consistent with recent theorizing (Craighead et al. ). Third, although supply chain research has generally found knowledge to be a performance driver (Wowak et al.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…Second, we shed light on how emerging market footholds accentuate performance by proposing that they facilitate the acquisition of strategically valuable market‐specific knowledge, consistent with recent theorizing (Craighead et al. ). Third, although supply chain research has generally found knowledge to be a performance driver (Wowak et al.…”
Section: Introductionsupporting
confidence: 74%
“…Using an emerging market foothold, a firm can create a presence in an emerging market (Craighead et al. ) while minimizing costs and associated risks. Through the emerging market foothold, the firm gains vital experience from which to build appropriate supply chain capabilities, putting it in a position to effectively expand in the market if conditions warrant.…”
Section: Background Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations